KAJIAN PERANCANGAN ARENA OLAHRAGA ELEKTRONIK - Thea Amelia; J.M. Joko Priyono Santoso (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2019)
Developing sports is characterized by the emergence of new sports, one of them is esports which also developing every year. The competition has been held at the 2018 Asian Games, however the venue has not been used specifically for esports. Therefore, the design of the esports arena is the answer and also the typical building that is present and marks the millennial generation of its time. Literature studies were conducted on millennial generation, behaviour of millennial, millennial era, building types and esports to find out more about the design of the esports arena. The methods used are data collection method, primary and secondary, quantitative and qualitative descriptive method, interaction method, comparative method, analytical and synthesis method, graphical method, experimental method conducted with theoritical studies, matrix studies, space studies, space characteristics studies, precedent studies, site studies and surveys, and mass compositions studies. The study resulted program area and capacity, site design, concepts, forms of mass composition, and schematic spatial principles (floor plan). Based on the methods and studies conducted, the conclusion is esports arena designed, in accordance with the theme "Dear Millennials, Dialogue between Type and Behavior" and programs in the form of esports arena, esports training rooms, plaza and cafeteria are programs that address spatial relationships between building types, millennial behavior and millenial era, as well as the design and concept of a centralized form, contrast, the existence of a plaza as a central space, technology space experience, and adaptive to the cyber theme responds to the influence of millennial behaviors and challenges. AbstrakOlahraga berkembang ditandai dengan munculnya cabang olahraga baru, salah satunya ialah esports yang juga sedang mengalami perkembangan tiap tahunnya. Kompetisinya pernah diselenggarakan pada Asian Games 2018, namun tempat penyelenggaraannya belum difungsikan secara khusus untuk esports. Oleh karena itu, perancangan esports arena menjadi jawaban dan merupakan bangunan khas milenial yang hadir dan menandai adanya generasi milenial pada zamannya. Kajian literatur dilakukan mengenai generasi milenial, perilaku milenial, nilai kesejamanan (milenial), tipe bangunan, dan esports untuk mengetahui lebih dalam mengenai perancangan esports arena. Metode yang digunakan adalah metode pengumpulan data, primer maupun sekunder, metode deskriptif kuantitatif maupun kualitatif, metode interaksi, metode komparatif, metode analisis dan sintesis, metode grafis, dan metode eksperimental yang dilakukan dengan studi kajian teori, studi matriks, studi ruang gerak, studi karakteristik ruang, studi preseden, studi dan survei tapak, dan studi gubahan massa. Studi tersebut menghasilkan luasan program dan kapasitasnya, rancangan tapak, konsep, bentuk gubahan massa, dan prinsip skematik keruangan (denah). Berdasarkan metode dan studi yang dilakukan, kesimpulannya ialah Esports Arena yang dirancang di Petojo Selatan, Jakarta Pusat, sesuai dengan tema “Dear Millennials, Dialogue Between Type and Behavior” dan program berupa esports arena, ruang latihan esports, plaza dan cafetaria merupakan program yang menjawab hubungan keruangan antara tipe bangunan, perilaku dan kesejamanan milenial, serta perancangan dan konsep bentuk yang memusat, kontras, adanya plaza sebagai ruang tengah, pengalaman ruang penuh teknologi dan menyesuaikan dengan tema cyber menjawab pengaruh dari perilaku dan tantangan kesejamanan milenial.